Junkzilla - Dadivas, Nonoy; Deocampo, Nick. ([Quezon City] Center for New Cinema, 1995)
A family witness the transformation of their garbage into a monster. The rubbish throw out of the window turns into a harmful creature that threatens the whole metropolis. Ordinary people become victims as the monster stalk at the night. The solutions given by adults do not put a stop to the threat posed by the garbage monster. It takes a child to finally save the whole community when he urges them to adopt proper garbage disposal.
DVD features: study guide ; photos video ; clips ; interviews and lectures ; essays ; PowerPoint.
Library has: VDR-1665 (1 DVD)
Audience sustainability: Elementary level.
DVD
Keywords: Waste minimization -- Juvenile films; Recycling (Waste, etc.) -- Juvenile films